The Effect of Stocking Density Differences on the Survival and Growth of Nile Tilapia (Oreochromis niloticus) Juveniles in a Bucket Aquaculture System (Budikdamber) - Anjany, Jeny Trysta; Herman, Roffi Grandiosa; Rostika, Rita; Zidni, Irfan (Jurnal Perikanan dan Kelautan, 2025)
Nile tilapia is one of Indonesia's leading aquaculture commodities, with strong potential for development to support food security and improve community welfare. This study aimed to analyze the effect of different stocking densities and to determine the optimal density that supports the survival and growth of Nile tilapia juveniles reared in the Budikdamber system. The research method used was an experimental method with a Completely Randomized Design (CRD), consisting of five treatments and three replications. The treatments were as follows: (A) stocking density of 15 fish/70 L (control), (B) 20 fish/70 L, (C) 25 fish/70 L, (D) 30 fish/70 L, and (E) 35 fish/70 L, maintained for 40 days with a feeding rate of 3% of the total biomass. Probiotics were applied at a dose of 0.8 ml/L through the culture water to maintain good water quality. The results showed that treatment B (20 fish/70 L) produced the best outcomes in terms of growth and survival, with an average absolute length gain of 2.03 ± 0.26 cm, absolute weight gain of 8.52 ± 1.11 g, a positive allometric length-weight relationship, a survival rate of 91.7%, a specific growth rate of 1.68 ± 0.17%, a feed conversion ratio of 1.59 ± 0.24, and water quality parameters within the acceptable range based on the Indonesian National Standard (SNI).